Zarządzanie kadrami w korporacji międzynarodowej - analiza empiryczna przypadku - Czubasiewicz, Halina; Nogalski, Bogdan (Human resource management in an international corporation - analysis based on practical experience, 2006)
The article provides a comparative analysis of the solutions applied in human resource management in the Polish branch of the international company - before and after the takeover. The analysis is carried out based on practical experience and reveals significant differences and various approaches used in practice. It shows that the approach characterized by the balanced level of centralisation and decentralisation of the activities concerning the staff issues prevails over the centralised approach.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 184-195